2011
DOI: 10.1029/2010jd015391
|View full text |Cite
|
Sign up to set email alerts
|

A downward positive leader that radiated optical pulses like a negative stepped leader

Abstract: [1] Using a high-speed optical imaging system (Automatic Lightning Progressing Feature Observation System (ALPS)) operated at a time resolution of 100 ns, we recorded a downward positive leader that radiated more than 20 optical pulses during its downward progression over the height from 299 m to 21 m above the ground like a negative stepped leader. The leader propagated at a speed of around 1.0 × 10 6 m/s over the height from 272 m to 93 m and then accelerated to a speed of 2.5 × 10 6 m/s at the height of abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…Nevertheless, analyzing the data of a positive CG lightning, Saba et al () reported that electric field pulses were observed only after the initiation of the upward negative stepped leader from the grounded structure and presumed the pulses to be due solely to the propagation of this negative leader. In a certain way, this is consistent with the observation by Wang and Takagi () of optical pulses propagating upward from the tip of the downward positive leader only after it reached 272 m above ground.…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalsupporting
confidence: 92%
“…Nevertheless, analyzing the data of a positive CG lightning, Saba et al () reported that electric field pulses were observed only after the initiation of the upward negative stepped leader from the grounded structure and presumed the pulses to be due solely to the propagation of this negative leader. In a certain way, this is consistent with the observation by Wang and Takagi () of optical pulses propagating upward from the tip of the downward positive leader only after it reached 272 m above ground.…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalsupporting
confidence: 92%
“…Considering that the electric field sensor was very close to the descending leader, that the charge carried by the leader was probably large and that the pulses observed initiate only when the negative upward connecting leader starts, we suggest that if positive leaders step (as in the case of the optical pulses of a positive leader reported by Wang and Takagi [2]), their steps do not produce any significant electromagnetic radiation and are much weaker than those produced by the stepping of the connecting negative leader.…”
Section: Discussionmentioning
confidence: 84%
“…Berger [1] using streak cameras has observed that positive leaders in general have no distinct steps, but show rather a periodic variation in light intensity and move in an apparently continuous manner. Wang and Takagi [2] recently observed, using a high-speed optical imaging system, a downward positive leader that radiated optical pulses like a negative stepped leader. According to the authors, the downward positive leader radiated more than 20 optical pulses during its downward progression over the height from 299 m to 21 m above the ground.…”
Section: Past Optical Observationsmentioning
confidence: 98%
“…The reason for the occurrence of field pulses indicative of stepping prior to the return stroke pulse in some positive cloud‐to‐ground discharges is not known. It could be associated with a descending positive leader, an upward connecting negative leader, which may be launched in response to the nonstepped positive downward leader, or both Wang and Takagi [2011]…”
Section: Leader Steppingmentioning
confidence: 99%